Medicinal plants from the Yanesha (Peru): Evaluation of the leishmanicidal and antimalarial activity of selected extracts - Céline V. (2009)
The authors gratefully acknowledge the financial assistance of CONCYTEC from Peru and DSF-IRD (JEAI) from France. We express our thanks to members of the Yanesha community who were willing to share with us their knowledge about medicinal plants. The authors are grateful to Candy Ruiz from LID-UPCH, for technical assistance in plants extractions. Céline Valadeau, Adriana Pabon and Denis Castillo received grants from the Institut Franc¸ ais des Etudes Andines, Colciencias and the Belgian technical cooperation respectively. Part of this work was supported by a grant from the International Foundation for Sciences attributed to Dionicia Gamboa